LEGAL PROBLEMS IN INDEPENDENCE REPRESENTING OPINIONS IN PUBLIC AND SOCIAL MEDIA AS DEFAMATION - Nanang Narundana, Joni (JILPR Journal Indonesia Law and Policy Review, 2024)
Identify legal problems that arise related to the freedom to express opinions in public and on social media as a potential for preventing defamation according to Law Number 19 of 2016 concerning Amendments to Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions. This research is a conflict between freedom of opinion and protecting an individual's good name in the context of existing regulations. The research method used is normative juridical analysis or reviewing existing legal documents and reviewing related literature. The research results show the complexity of interpreting the law, which requires a balance between freedom of expression and protection of individual honor. The implication of this research is the need for careful and contextual interpretation of laws to avoid abuse and maintain a balance between individual rights and societal interests in the digital space.